2006
DOI: 10.1002/dvdy.20917
|View full text |Cite
|
Sign up to set email alerts
|

Three Dact gene family members are expressed during embryonic development and in the adult brains of mice

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 31 publications
4
96
0
Order By: Relevance
“…Three Dpr family members, Dpr1, Dpr2, and Dpr3, have been described in mammals (23), and they appear to have distinct functions. Human Dpr1 as well as Dpr3 can inhibit Wnt signaling by promoting Dvl degradation (14,24,25).…”
mentioning
confidence: 99%
“…Three Dpr family members, Dpr1, Dpr2, and Dpr3, have been described in mammals (23), and they appear to have distinct functions. Human Dpr1 as well as Dpr3 can inhibit Wnt signaling by promoting Dvl degradation (14,24,25).…”
mentioning
confidence: 99%
“…Three Dact family members (Dact1-3) have been identified in vertebrates (25), where based on a variety of in vitro and in vivo assays, they appear to have both overlapping and divergent signaling functions (26 -31). In studies using genetically engineered mice, we have shown previously that Dact1 is required for normal post-translational regulation of Vangl2 during the epithelial-mesenchymal transition at the primitive streak, for normal PCP in posterior embryonic tissues, and that defects in these developmental processes in Dact1 null embryos lead to complex birth malformations, including NTDs (29).…”
mentioning
confidence: 99%
“…The importance of this range, which would allow students to be active, focused, and engaged, has been addressed from a variety of theoretical perspectives-the Zone of Proximal Development (Vygotsky, 1978), functional-optimal performance (Fischer & Bidell, 2006), and Flow (Csikszentmihalyi & Rathund, 1998). During the first two years that we taught the course, the questionnaires evolved in minor ways, mostly to increase the clarity of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Howe, Devine and Tavares (2013) summarized three potential issues with the classic framework when researchers reported limited success with an intervention: "(a) experiments often fail to generate the requisite data; (b) Posner et al's (1982) [first] three conditions may be necessary, but they are insufficient; and, (c) cognitive limitations eclipse the significance of experimental evidence" (p. 865). The last point has been a central focus in the cognitive sciences to understand cognitive limitations from a developmental point of view and to explain the movement from disequilibrium to equilibrium as a dynamic process that evolves as the mind and brain mature (Fischer & Bidell, 2006;Schwartz, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%